Reply letter to "response to article by Johnna Perdrizet et al." by Gomez and colleagues - Johnna Perdrizet; Carlos Felipe S. Santana; Thais Senna; Rodrigo Fernandes Alexandre; Rodrigo Sini de Almeida; Julia Spinardi; Matt Wasserman (Taylor & Francis Group, 2022)
This communication seeks to address the questions and criticisms issued by Gomez and colleagues in their letter on our original study "Cost-effectiveness analysis of replacing the 10-valent pneumococcal conjugate vaccine (PCV10) with the 13-valent pneumococcal conjugate vaccine (PCV13) in Brazil infants." Gomez and colleagues are concerned that the assumptions used in our model may have unintended negative impacts for Brazil decision-making and we intend to clarify any potential misinterpretation of our assessment.